Nitrogen recycling from fuel-extracted algal biomass: Residuals as the sole nitrogen source for culturing Scenedesmus acutus. (May 2015) - Gu, Huiya; Nagle, Nick; Pienkos, Philip T.; Posewitz, Matthew C.
Highlights: Algal fermentation residues (SABCr) were enriched in proteins and amino acids. SABCr could replace nitrate as the sole nitrogen source to grow Scenedesmus acutus . Substitution of SABCr for nitrate enhanced Scenedesmus growth and lipid production. Selected strains showed different abilities to assimilate organic nitrogen sources. Abstract: In this study, the reuse of nitrogen from fuel-extracted algal residues was investigated. The alga Scenedesmus acutus was found to be able to assimilate nitrogen contained in amino acids, yeast extracts, and proteinaceous alga residuals. Moreover, these alternative nitrogen resources could replace nitrate in culturing media. The ability of S. acutus to utilize the nitrogen remaining in processed algal biomass was unique among the promising biofuel strains tested. This alga was leveraged in a recycling approach where nitrogen is recovered from algal biomass residuals that remain after lipids are extracted and carbohydrates are fermented to ethanol. The protein-rich residuals not only provided an effective nitrogen resource, but also contributed to a carbon "heterotrophic boost" in subsequent culturing, improving overall biomass and lipid yields relative to the control medium with only nitrate. Prior treatment of the algal residues with Diaion HP20 resin was required to remove compounds inhibitory to algal growth.